For an inclusive education: the innovative challenge of technologies for social emotional learning - Annalisa Morganti; Stefano Pascoletti; Alessia Signorelli (Firenze University Press, 2016)
The paper presents a collection of national, European and international evidence intended to identify the efficacy of social and emotional learning, of educational technologies, with a focus, in both cases, on inclusive processes. The paper, that is the outcome of the joint work of the authors, investigates the added, potential value given by technology to social and emotional learning, through different tiers of actions and the main features of ed-tech that can support such a use. Per un'educazione inclusiva: la sfida innovativa delle tecnologie per l'educazione socio-emotiva Il contributo presenta una raccolta di evidenze nazionali, europee ed internazionali, volte a individuare l'efficacia, dell'educazione socio-emotiva, delle tecnologie per la didattica, con un'attenzione, in entrambi i casi, ai processi inclusivi. Frutto del lavoro congiunto degli autori, il contributo indaga il valore aggiunto che la tecnologia può offrire all'educazione socio-emotiva, su differenti piani di azione e le principali caratteristiche ed-tech che possono supportarne tale utilizzo.